Respon Beberapa Rumput Unggul pada Lahan Perkebunan Kelapa Sawit di Kelurahan Kenali Asam Atas Kecamatan Kota Baru Jambi - Farizaldi, Farizaldi (Fakultas Peternakan Universitas Jambi, 2011)
The aim of this research is to know about response some superior grass that is groun up with gaps in palm oil plants and compore in with superior grass that groun up without gaps in oil palm plants. This research uses three kind of superior grass. They are king grass (Pennisetum purpupoides), elephant grass (Pennisetum purpureum) and setaria grass (Setaria splendida). The method that is used in this research is descriptive statistics and than diversity trial done by using test t to compore the result which is gotten with gaps or without gaps in palm oil plants (Steel and Torrrie, 1993). The research results shown that quantity of smaller variant plants , high plants and forage dry matter production that groun up with gaps in palm oil plants is not different clearly ( p > 0.05) with forage that is groun up without gaps in palm oil plants. Based on research result, we can conclude that king grass, elephant grass and setaria grass growth which groun up with gaps in palm oil is not different clearly with this plants that groun up without gaps in palm oil.